Long Noncoding RNAs, New Critical Regulators in Cancer Immunity - Wu, Minjie; Fu, Peifen; Qu, Lei; Liu, Jian; Lin, Aifu (Frontiers in Oncology, 2020)
Long noncoding RNAs (LncRNAs) play crucial roles in various aspects of cellular functions. Recent studies have revealed that lncRNAs are critical players in the immune system by modulating immune cell differentiation and functions, particularly in cancer immunity. Here we systematically summarized how lncRNAs were involved in different processes of cancer immunity cycle, including immune cell differentiation, proliferation, trafficking, and infiltration. Moreover, the limitations of the current understanding of lncRNA’s functions in cancer immunity are described, such as the complexity of the cancer immunity system, the inclusive functions of lncRNA in this system and the associated immune response. In sum, the comprehensive investigation of the roles lncRNAs in cancer immunity aids in cancer diagnosis and therapies.